Advances in spatial economic data analysis: methods and applications. Issue 2 (3rd April 2021) - Piacentino, Davide; Arbia, Giuseppe; Espa, Giuseppe
ABSTRACT: Spatial economic studies traditionally exploit areal data at the regional or sub-regional level. More recently, scholars have started to exploit spatial data of a different nature and, at the same time, extend the fields of application in economics. Specifically, this special issue contributes to the spatial economic literature by providing empirical evidence on a wide range of phenomena (socio-economic deprivation, land price volatility, electoral competition, real estate market, firm survival and tourism economics) and exploiting data at the municipality, firm, house and even individual level. At the same time, it tackles some of the methodological issues faced by the above-mentioned analyses.